Das Schadensersatzrecht der §§ 249 ff. BGB im Lichte der französischrechtlichen responsabilité civile - Pache, Stephan (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
The work compares the German law of damages with the French responsabilité civile, taking into account several French reform projects as well as European regulatory approaches. The work is intended to provide an input to reflection for a potential European Civil Code. In addition to the introduction and the result, it is divided into 4 main parts, in which the conditions and legal consequences of the claim for damages are examined. In addition, the work is devoted to the grounds for reduction and exclusion of claims for damages as well as the law of evidence. The thesis is aimed at academics, practitioners and students.